Analysis And Implementation of Simple Queue and Queue Tree Methods For Optimizing Bandwitdh Management - Muhammad Ibrahim Nasution; Febria Rahim; Habib Alfarizzi (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2022)
This study analyzes the Simple Queue method with Queue tree using a Mikrotik Router to perform Bandwidth management. Both of these methods will be tested using the parameters of Quality of Services ( QOS ), namely throughput, delay, jitter and packet loss. The results of the analysis of the Quality of Services will be compared with weighting based on the TIPHON standard, then the results of the analysis will be tested using the wireshark application . The results of the analysis of these two methods, the Simple Queue method is more suitable because it gets a higher value based on the TIPHON standard. Therefore it is recommended to use Bandwidth management using the Simple Queue method